Prediction of Operational and Emergency States of Rocket Equipment Critical Systems Under Repeated Thermal and Power Load - Shevchenko, Yu.N.; Andrushko, N.F.; Babeshko, M.Ye.; Banias, M.V.; Galishin, A.Z.; Dehtyarenko, P.G.; Savchenko, V.G.; Tonkonogenko, A.M.; Tormakhov, N.N. (Science and Innovation, 2024)
A mathematical model for studying the thermal elastic and plastic stress-strain state and the strength of the rocket equipment systems at restarts has been proposed using the heat conductivity equations and the constitutive equations of thermal plasticity for repeated elastic-plastic strains of isotropic materials along small-curvature trajectories, the strength and low-cyclic fatigue criteria, numerical methods for solving the boundary heat conductivity problems, as well as special software.